Prospecção e seleção de agentes de controle biológico para manejo doenças em milho com foco em redução de grãos ardidos - Zanotto, Edgar (2014)
Rot grains reduces corn quality and maximum value acceptable are 2% for exports and 6% for internal market. Moreover, they cause reduction in the commercial value of grains which usually is deducted at the time of delivery to storage. Colletotrichum graminicola, Stenocarpella maydis , Fusarium graminearum and Fusarium verticillioides has been described as main agents to produce rot grains on field. In another hand, Aspergillus and Penicillium are the main cause after harvest. The objective of this study was to find biological control agents to management of diseases in corn, focusing on the reduction of rot grains. The prospection of the isolates was performed by the method of naturally infected bait. It was conducted a pretest in prospected isolates from direct inhibition against F. verticilioides. The isolates obtained in the previous step, along with isolated provided by Embrapa were evaluated for grain protection capability inoculated with A. flavus and F. verticillioides. To assess the field efficiency, four experiments were carried out in two different areas and two seasons. The antagonists selected in the previous steps were applied as a suspension in two stages of plant development. The first application was in the early stage V9-10 and the second pre- silking(R1 stage) . After 10 days of the issue of stigma style F.verticillioides was sprinkled on the stigma style. The treatments, in the field, consisted by PRIORI XTRA + PRIORI XTRA, Streptomyces + PRIORI XTRA, PRIORI XTRA + Streptomyces, BIOUFLA2+BIOUFLA2, Streptomyces + Streptomyces, PRIORI XTRA, PRIORI XTRA + BIOUFLA2, BIOUFLA2 + PRIORI XTRA and Control. The experiments were a randomized block with four replications for each treatment. Were evaluated the corn diseases in the field, culture productivity, rot grains and sanity of grains.The results showed consistent on the experiments carried out. The use of actinomycetes Streptomyces araujoniae in the management of the corn crop has shown great results for foliar diseases, as well for the reduction of rot grains.